Influence of nutritional status on the clinical outcome of patients with chronic subdural hematoma: a prospective multicenter clinical study. (3rd August 2022) - Scerrati, Alba; Pangallo, Giulia; Dughiero, Michele; Mongardi, Lorenzo; Ricciardi, Luca; Lofrese, Giorgio; Dones, Flavia; Cavallo, Michele Alessandro; De Bonis, Pasquale
ABSTRACT: Background: Elderly patients present a higher risk of developing chronic subdural hematomas (CSDHs) together with increased risk of malnutrition. The nutritional status may affect outcomes, response to treatments, and prognosis. Influence on other kinds of diseases was investigated showing an increased risk of mortality, morbidity, and adverse outcomes. However, no studies are available on its possible role for the outcome of patients with CSDH. This study aims to evaluate a possible relationship between the nutritional status and the clinical outcome of patients who underwent CSDH surgery. Methods: This is a multicenter prospective study enrolling all patients treated for CSDH. Demographic and clinical data were collected. For nutritional status evaluation, we used the Mini Nutritional Assessment (MNA). Chi-square test was used for comparing clinical variables of patients and logistic regression analysis was used for defining the impact of the aforementioned variables on the clinical outcome. Results: We enrolled 178 patients. Modified Rankin scale (mRS) was 0–2 pre-operatively in 23.6% of patients and post-operatively in 61.2% of patients. Total assessment MNA score was >23.5 in 47.8% of patients. Ninety-three patients (52.2%) presented a normal nutritional status, 63 (35.4%) were at risk of malnutrition and 22 (12.4%) were malnourished. The mean follow-up was 2.6 months. Malnourished patients were at higher risk of a worse outcome (OR 81; CI = 9-750). Conclusion: This study suggests that nutritional status represents a strong predictor of outcome. Our results, albeit preliminary, demonstrated malnutrition is correlated to the risk of worse clinical outcome for patients undergoing surgery for chronic subdural hematoma. Further investigations with wider casuistry and multiple nutritional scores are required to validate our data.